Calculated Radioactivity Yields of Cu-64 from Proton-Bombarded Ni-64 Targets Using SRIM Codes - I. Kambali (PPIKSN-BATAN, 2014)
The End-Of-Bombardment (EOB) Yields from 64Ni(p,n)64Cu nuclear reaction have been calculated for optimizing irradiation parameters that correspond to future 64Cu radionuclide production using the BATAN’s 26.5-MeV cyclotron in Serpong. Enriched Ni target thickness, proton beam current and irradiation time which play significant role in the success of the Positron Emission Tomography (PET) radionuclide were also discussed in this paper. For a 26.5-MeV proton beam, the optimum target thickness for 64Cu production was nearly 1.5 mm with yields up to 560 mCi/µA.hr at the end of the irradiation. The comparisons with some selected experimental data indicated that the much-lower-than-expected EOB yields were mainly due to incorrect target thickness prepared for the irradiation. Nevertheless, these calculations were in good agreement with the previous predicted data with a maximum difference of less than 10%. The discrepancies were mostly due to different cross-section data employed in the calculations.Received: 23 October 2014; Revised: 24 December 2014; Accepted: 27 December 2014